The determination of dairy farms in terms of some factors affecting Biosecurity in Malatya - Şeker, Ibrahim; Köseman, Abdurrahman; Mundan, Durhasan (Ataturk Universitesi, 2017)
This research was conducted to determine some factors that affect the biosecurity of dairy farms which have 50 and over head cows in Malatya. For this purpose, investigations and evaluations were held in farms and face to face interviews were applied with 78 breeders selected by using the random sampling method. It is found that the ratio of the existence of managing buildings, security camera in the business, and grid channel system for manner transferring in shelters are respectively 16.7%, 17.9% and %9.0%. The usage of automatic drinkers and grooming brushes are calculated respectively 43.6% and 57.7%. It is estimated that the ratio of the sanitation of shelters is 89.7% and adequate vantilation is 92.3%. In conclusion, it is determined that some applications and changes are required to maintain a sufficient level of biosecurity. To consider and resolve the problems, it was concluded that training and informing all the staff and the managers in earnest, applying the administrative sanctions effectively as well as controlling and inspecting more actively was necessary.
Biyogüvenlik için gerekli bazi faktörler bakimindan malatya ili süt si?ircili?i işletmelerinin de?erlendirilmesi
Keywords: Biosecurity; Dairy farms; Hygiene; Training